"Not an Either/or Situation": The Minimization of Violence Against Women In United Kingdom "Domestic Abuse" Policy. (September 2021) - Aldridge, Jo
Proposed new legislation in England and Wales on domestic violence and abuse—the "Domestic Abuse Bill"—is underpinned by changes to criminal law, specifically the introduction of coercive and controlling behavior as set out in the Serious Crime Act 2015. The new Bill commits the British government to four main objectives with, it is claimed, prevention and protection at their heart. What is notable, however, is the rubric shift from "violence" to "abuse" in the proposed new legislation and its subscription to a gender symmetry paradigm that suggests a "watering down" of the government's response to gendered violence.